NCOG-34. AN ASSESSMENT OF OVERALL SURVIVAL AND PALLIATIVE CARE USE AMONG PATIENTS WITH GLIOSARCOMA DIAGNOSED OVER A TWELVE-YEAR SPAN. (9th November 2020) - Boisclair, Stephanie; Samuels, Shenae; Raez, Luis E; Wietecha, Delia A; Cohen, Alejandro Lopez; Khunger, Arjun; King, Kelly; Sareli, Candice; Adames, Jorges; Jacques, Jessica; Salzberg, Mathew; Hunis, Brian; et al.
Abstract: Gliosarcoma (GS), a rare variant of glioblastoma, accounts for less than 5% of CNS tumors. Due to its low incidence and prevalence, very few comprehensive, large-scale studies are reported in the literature that describe prognostic elements and treatment outcomes. The objective of the study was to examine patient and treatment characteristics to identify significant predictors of survival. METHODS: Data on patients with GS, diagnosed between 2004-2016, was extracted from the National Cancer Database (NCDB). Univariate analysis and a multivariate Weibull regression model was used to determine prognostic factors of survival (months). Kaplan-Meier (KM) method with log-rank test was used to compare and estimate overall survival rates between various groups. RESULTS: There was a total of 2, 656 GS patients identified in the NCDB between the years of 2004-2016 with median age of 62 years old. In multivariable Weibull regression model, increasing age (HR=1.04, p=0.000) and increasing comorbidities were independent predictors of increased hazard of death. Having 3 or more comorbidities had the strongest association with increased hazard of death (HR=1.44; P =0.001). The OS has minimally improved over the period of 2004-2016; median OS was highest among those diagnosed between 2012 and 2016 at 11.4 months followed by an OS of 10.6 months between 2004 and 2007, and 9.1 months between 2008 and 2011 ( P =0.001). Although current clinical guidelines recommend chemotherapy and radiation within 30 days of surgery, there was no statistically significant difference in median OS between patients who had chemotherapy initiated within 30 days, between 30 and 60 days or later than 60 days ( P =0.109). There is also no statistically significant difference in OS for time of radiation initiation categories ( P =0.752). In a disease with such low OS and limited treatment options, palliative care use was found in only 45 (1.7%) patients.